Building Resilience Against Leptospirosis through Engagement Community and Private Sector - Astari, Lusha Ayu; Sandi, Novra Arya; Diva, Haniena; Yuwanto, Indra Dwi Octa (BKM Public Health and Community Medicine, 2024)
Purpose: This paper aims to delineate a strategic framework for combating leptospirosis in Bantul District by enhancing resilience through active community and private sector engagement. Content: Leptospirosis has become the threat year-round in Bantul District, Yogyakarta, thus needing more than the seasonal interventions. However, due to its growth and constant cases from 120 in 2021 to 175 in 2023, more of this disease requires control measures all year round and integrated strategies. This position paper shifts focus to different clients involved in pest management such as healthcare provider, local administrators and most importantly the community members and private entrepreneurs. It then calls for a cross-system improvement collaboration model that entails the District Health Office and Environmental Services Department, as well as other stakeholders. This new strategy seeks to move from fragmented and acute approach to a systematic and long-term strategy of improving the community capacity for education, involvement, and advocacy. Due to the increased engagement of the people in the community and specialists in pest management, the model aims at increasing the level of compliance as well as efficacy of the measures taken. This work not only seeks to enhance implementation of leptospirosis control in Bantul but also proffer a template for handling other similar public health issues across the world to show the need for strong, synergy between government departments, non-governmental agencies and other stakeholders for best results.